RESPIRATORY FUNCTION IN PATIENTS WITH RHEUMATIC HEART DISEASE COMPLICATED WITH PULMONARY HYPERTENSION - N. A. Shostak; A. A. Klimenko; I. A. Novikov (Столичная издательская компания, 2016)
Aim. To evaluate the changes of respiratory function in patients with rheumatic heart disease (RHD) complicated with pulmonary hypertension (PH) by the spirographic investigation. Materials and methods. Patients (n=56; 4 men and 52 women; aged 63,25±7,93) with rheumatic combined mitral and aortic valvular disease were examined. Medical history analysis, physical examination, general clinical investigation including ECG, chest X-ray, 2D-echocardiography and spirography were performed.  Results. 36% of the patients had normal pulmonary arterial systolic pressure (PASP) (<30 mm Hg), 48% had PH of degree I and 16% - PH of degree II. Restrictive changes of spirogram were found in 27% of patients: in 30% of patients with PH of degree I, in 44% of patients with PH of degree II and in 5% of patients with no PH. Bronchoobstruction was detected in no one patient. Pulmonary restriction significantly (p<0,05) correlated with PH, but no significant difference was found between groups with PH of I and II degree. No any association between PASP, spirogram changes and type of valvular lesion was revealed. Conclusion. Patients with RHD complicated with PH have pulmonary restrictive changes according to spirographic investigation.